Comparison of two gel filtration chromatography resins for the purification of foot-and-mouth disease virus as a purified vaccine antigen - P Hosseini; H Mahravani; M Azimi; S Shahsavandi (Vaccine Research, 2016)
Introduction: Foot-and-mouth disease (FMD) is a highly contagious and economically devastating viral disease of livestock that is categorized in list A of animal diseases by the World Organisation for Animal Health (OIE). Vaccination is effective against FMD and the vaccine production centers largely use the industrial ultra-filtration and chromatography in order to remove the cellular proteins as well as the non-structural viral proteins. The recommended method for the purification and quantification of the active ingredient of vaccines is 140S quantitative sucrose density gradient analysis. Despite many advantages, this method is highly operator-dependent and is not suitable for large-scale vaccine productions. The main objective of this study was to compare and evaluate two chromatography resins (i.e. Sephacryl S-300 and Sephacryl S-500) to separate FMD virus particles from the non-structural viral proteins. Methods: The resins were compared for gel filtration chromatography and the virus infectivity titration (CCID50% / ml) and real-time PCR amplification analyses were performed. Results: The results indicated that Sephacryl S-500 was not able to separate blue dextran from bovine serum albumin; therefore, it was not suitable for separation of the whole virus from the non-structural proteins while Sephacryl S-300 was suitable for this purpose. Conclusion: Sephacryl S-300 is a suitable resin for preparation of purified virus for large-scale FMD vaccine production.